(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
The cyclone fields moving from the Cyprus Regions to the Republic of Armenia have great influence on the formation of weather conditions of the Republic especially in cold period of the year. The origin of strong winds, snowstorms and heavy rain is conditioned by them. The conditions of the Cyprus Cyclone formation, the features of the speed and the direction of the movement, the peculiarities of weather conditions in its different parts have been studied on the basis of synoptic charts, satellite photos and other statistical data. They are in the archives of the Hydrometeorological Centre of Armenia.